Knowledge, attitudes and misconceptions of Italian healthcare professionals regarding fever management in children - Elena Chiappini; Antonina Marta Cangelosi; Paolo Becherucci; Monica Pierattelli; Luisa Galli; Maurizio de Martino (BMC, 2018)
Abstract Background Fever phobia is still a major issue in paediatrics. We report knowledge of a sample of Italian paediatricians performed six years after the release of the Italian guidelines for the management of fever in children (IFG). Methods A questionnaire, developed following the IFG recommendations and previously administered to 300 paediatricians in 2012, was proposed to all the paediatricians attending the 2015 National Congress of Practice Paediatrics, held in Florence, Italy. Changes in answers over time were analyzed. Results 70.2% (562/800) paediatricians returned the questionnaire. The recommended site and device for body temperature measurement in children > 1 year was correctly chosen by 89.3% of participants (vs. 80.7% of 2012 participants; P < 0.001), but with children aged less than 1 year the correct answer was selected only by the 50.3% (vs. 39.3% of 2012 participants: P < 0.001). Use of physical methods was still incorrectly recommended by 51.6% of paediatricians (vs. 63.6% in 2012; P < 0.001). Use of antipyretics according to discomfort was adopted only by 38.2% of participants, while 12.2% of them recommended alternate use of antipyretics. These proportions were substantially stable since 2012 (45 and 11% respectively), rectal administration of antipyretics only in case of vomiting was correctly recommended by 86.8% of paediatricians vs. 74.7% in 2012 (P < 0.001). Conclusion Improvements in some pediatricians' misconceptions were observed over time. However, some incorrect habits persist. Further studies are needed to better understand the "weak points" of the communication between Scientific Societies and paediatricians in order to impact everyday clinical practice.